THE EFFECT OF LEGAL EDUCATION ON STUDENTS’ UNDERSTANDING OF THE DANGERS AND IMPACTS OF BULLYING AT MA AL-HASANY IN PONTIANAK FROM A CHILD PROTECTION PERSPECTIVE - Toni; Lubna; Fatimatuzzahroh; Meysa; Arf; Dita; cinta; Vahriatul Zunaira (Jurnal Ikhtibar Nusantara, 2026)
Bullying is a serious social phenomenon that threatens the psychological development and legal awareness of adolescents, particularly in Islamic educational institutions. This issue arises due to peer pressure, digitalization, and the weakening of legal and moral awareness among students. This study aims to analyze the effectiveness of empirical-based legal counseling in enhancing students’ understanding and legal awareness regarding the dangers and impacts of bullying at MA Al Hasany Pontianak. The research employed a qualitative approach consisting of three main stages: planning, implementation, and evaluation. Data were collected through observation, interviews, and interactive discussions with students and teachers. The findings revealed that 68% of students were previously unaware of the legal sanctions related to bullying under the Child Protection Law, and 72% did not understand the legal consequences of cyberbullying. After the legal counseling program, there was a significant improvement in students’ legal understanding, preventive awareness, and reflective behavior. The empirical-based legal counseling also strengthened collaboration among madrasah, teachers, and parents in character development and child protection. Therefore, empirical legal counseling is considered an effective preventive educational model for shaping a law-abiding, ethical, and morally responsible young generation.